Cost‐effectiveness analysis of home‐based rehabilitation compared to usual care for people with inoperable lung cancer. (15th August 2021) - Edbrooke, Lara; Denehy, Linda; Patrick, Cameron; Tuffaha, Haitham
Abstract: Objective: Few economic evaluations of lung cancer rehabilitation exist. The aim of this study was to assess the cost‐effectiveness of providing home‐based rehabilitation for inoperable lung cancer. Methods: A cost‐utility analysis alongside a randomised controlled trial (RCT) of rehabilitation compared with usual care. The primary outcome was quality‐adjusted life years (QALYs) gained. The incremental cost‐effectiveness ratio [ICER (95% CI)] and the net monetary benefit are reported. Value of information (VOI) analysis assessed the need/value of more research. Results: Seventy participants (34 intervention and 36 usual care), average (SD) age 63.0 (12.0) years, 32 (45.7%) stage IV. The average intervention cost was AU$3421 (AU$5352 usual care), and effect (QALY) was 0.30 (0.31 usual care). The ICER was AU$228, 197 (−1, 173, 194 to 1, 101, 450) per QALY gained. The net monetary benefit was AU$1508, favouring the intervention. The probability that the intervention was more cost‐effective than usual care, at a willingness to pay threshold of AU$50, 000, was 75%. VOI analysis showed that additional research to resolve decision uncertainty is potentially worthwhile. Conclusion: A high degree of uncertainty exists regarding the cost‐effectiveness of lung cancer rehabilitation. Further RCTs, powered for economic evaluations and utilising rehabilitation sensitive outcomes, are required to support translation of evidence into clinical practice.